ANALYSIS OF THE FINANCIAL HEALTH OF RURAL CREDIT BANKS BEFORE AND DURING THE COVID-19 PANDEMIC (Case Study of the Implementation of Financial Risk Management at Bank Perkreditan Rakyat Nusantara Bona Pasogit 20) - Jona Sitepu; Nisrul Irawati; Isfenti Sadalia (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The Covid-19 pandemic has impacted the business industry, especially the banking sector. This study aims to analyze the financial health of Rural Banks before and during the Covid-19 pandemic. Another objective of this research is to describe the implementation of risk management during the COVID-19 pandemic. The object of this research is the Bank Perkreditan Rakyat Nusantara Bona Pasogit 20 (BPR NBP 20). This research method is quantitative by comparing the financial health proxied by non-performing loans, return on assets, operating expenses to operating income, cash ratio and loan to deposit ratio. Qualitative research methods describe the implementation of risk management during the Covid-19 pandemic. The results showed that there were statistical differences in financial performance statistics before and during the Covid-19 pandemic period for financial performance as measured by non-performing loans, return on assets, cash ratio and loan to deposit ratio, and there were no statistical differences for financial performance as measured by operating expenses to operating income. The results of research on the implementation of risk management in the first semester of the Covid-19 pandemic period were in adequate condition, and BPR NBP 20 regularly reported the results of risk assessments to the Financial Services Authority (OJK).